2019
DOI: 10.1016/j.csbj.2019.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Current computational methods for predicting protein interactions of natural products

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 144 publications
(147 reference statements)
0
35
0
Order By: Relevance
“…Amongst the reported HDAC inhibitors from nature are the macrocyclics; romidepsin and largazole, having a thiol ZBG in their activated forms [27] . In this regard, substructure searching, [24g] which represents a simple but powerful tool in drug discovery to perform initial filtration of molecules implemented in our online database was used to search for molecules with a thiol group, sulphur containing ZBG or sulphur‐containing molecules that can also be activated to HDAC inhibitors.…”
Section: Methodsmentioning
confidence: 99%
“…Amongst the reported HDAC inhibitors from nature are the macrocyclics; romidepsin and largazole, having a thiol ZBG in their activated forms [27] . In this regard, substructure searching, [24g] which represents a simple but powerful tool in drug discovery to perform initial filtration of molecules implemented in our online database was used to search for molecules with a thiol group, sulphur containing ZBG or sulphur‐containing molecules that can also be activated to HDAC inhibitors.…”
Section: Methodsmentioning
confidence: 99%
“…The off-target effect of a small molecule predicts not only the possible side effect but also the phenotypic outcome [163]. With the development of structural biology and computational methods, structures of targets and small molecules can be used to predict the off-target effect, providing a fast and economic way to evaluate the safety of the compounds [164].…”
Section: Characterization Of On-and Off-target Effectsmentioning
confidence: 99%
“…Compounds 1-3, 5, 7, and 12 were identified as the most potentially cytotoxic agents. We utilized cheminformatics techniques [51][52][53][54] to predict the most probable drug targets of these compounds. The kyoto encyclopedia of genes and genome (KEGG) database showed that seven major cancer drug targets are associated with triple-negative breast cancer including epidermal growth factor receptor (EGFR), proto-oncogene tyrosine-protein kinase Kit (c-KIT), insulin-like growth factor receptor 1 (IGFR1), notch receptor 1 (notch 1), phosphatidylinositol-3,4,5-trisphosphate-3-phosphatase (PTEN), phosphatidylinositol-4,5-bisphosphate 3-kinase (PI3K), and cyclin-dependent kinase 4 (CDK4).…”
Section: Human Intracellular Drug Targetsmentioning
confidence: 99%